Additive-free red phosphorus/Ti3C2Tx MXene nanocomposite anodes for metal–ion batteries. (24th October 2022) - Subramaniyam, Chandrasekar M; Kang, Min-A; Li, Jian; VahidMohammadi, Armin; Hamedi, Mahiar Max
Abstract : We report an environmentally benign, and additive-free red P/Ti3 C2 T x MXene nanocomposites as high-performance anodes for alkali-metal–ion batteries (MIBs where M = Li +, Na +, K + ). Abstract : Herein, we report on scalable, environmentally benign, and additive-free, high-performance anodes for alkali–metal–ion batteries (MIBs, where M = Li +, Na +, K + ). The intercalators in these anodes are the red phosphorus (RP) nanoparticles of uniform size (∼40 nm), which are dispersible and blend with water-dispersed Ti3 C2 T x MXene, forming a highly viscous aqueous slurry to fabricate additive-free nanocomposite electrodes. We further enhanced their performance using a very low weight percentage of various carbonaceous nanomaterials. Our RP-MWCNT/MXene nanocomposite anodes exhibited enhanced ion transport and low charge transfer resistance, delivering specific capacities of 1293.7 mA h g −1 at 500 mA g −1 and 263.3 mA h g −1 at 2600 mA g −1 for 10 000 cycles in Li + cells, 371.6 mA h g −1 at 500 mA g −1 in Na + cells, and 732.8 mA h g −1 at 50 mA g −1 in K + cells. Our work shows a path towards fabricating nanoarchitectured electrodes using sustainable materials to eliminate inert polymer binders, toxic processing solvents, and rare earth elements from the battery fabrication process for next-generation alkali–metal–ion batteries.